Transcriptomic and physiological analyses reveal different grape varieties response to high temperature stress - Feifei Dou; Fesobi Olumide Phillip; Gang Liu; Jingjing Zhu; Lipeng Zhang; Yongkang Wang; Huaifeng Liu (Frontiers in Plant Science, 2024)
High temperatures affect grape yield and quality. Grapes can develop thermotolerance under extreme temperature stress. However, little is known about the changes in transcription that occur because of high-temperature stress. The heat resistance indices and transcriptome data of five grape cultivars, ‘Xinyu’ (XY), ‘Miguang’ (MG), ‘Summer Black’ (XH), ‘Beihong’ (BH), and ‘Flame seedless’ (FL), were compared in this study to evaluate the similarities and differences between the regulatory genes and to understand the mechanisms of heat stress resistance differences. High temperatures caused varying degrees of damage in five grape cultivars, with substantial changes observed in gene expression patterns and enriched pathway responses between natural environmental conditions (35 °C ± 2 °C) and extreme high temperature stress (40 °C ± 2 °C). Genes belonging to the HSPs, HSFs, WRKYs, MYBs, and NACs transcription factor families, and those involved in auxin (IAA) signaling, abscisic acid (ABA) signaling, starch and sucrose pathways, and protein processing in the endoplasmic reticulum pathway, were found to be differentially regulated and may play important roles in the response of grape plants to high-temperature stress. In conclusion, the comparison of transcriptional changes among the five grape cultivars revealed a significant variability in the activation of key pathways that influence grape response to high temperatures. This enhances our understanding of the molecular mechanisms underlying grape response to high-temperature stress.